Technology of converted cast with electric influence on tank - S. I. Semykin; V. F. Poljakov; E. V. Semykina; A. D. Zrazhevski; V. I. Pishchida; S. N. Kravets; S. S. Brodski; L. M. Uchitel (Литьë и металлургия)
In the Institute of ferrous metallurgy of the National^ Academy of Sciences of the Ukraine there is developed the new technology, provided for application of electric energy of I low capacity, which allows to use more fully the potential capabilities of melting processes and out-of-fumace processing of metal. There is established the essential improvement of \ converter melting indices as regards of resource economy, heightening of tank heat content, lowering of sulfur, phosphorus, nitrogen, oxygen content in melt, and also improvement of \ ecological indices of the process. There is shown the possibility of increase of degree of metal refining from detrimental impurities at dipper processing.